2023
DOI: 10.1002/aenm.202203952
|View full text |Cite
|
Sign up to set email alerts
|

A Goldilocks Approach to Water Management: Hydrochannel Porous Transport Layers for Unitized Reversible Fuel Cells

Abstract: sources, such as wind and solar, are intermittent in nature, and must be combined with large-scale energy storage to provide stable and reliable power. Hydrogen-based reversible fuel cells (RFCs), which combine the functionality of a polymer electrolyte membrane (PEM), fuel cell (FC), and water electrolyzer (WE), could play a crucial role in providing this energy storage. During periods of excess renewable power generation, RFCs can electrolyze water to generate hydrogen. During periods of excess demand and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Neutron imaging is a valuable complement to X-ray imaging, since neutrons can penetrate common metals while attenuating hydrogen, lithium, and water. This feature makes neutron imaging an attractive technique for characterizing various electrochemical systems, including fuel cells, water electrolyzers, unitized reversible fuel cells, and CO 2 electrolyzers . Moreover, neutron imaging is particularly well-suited for imaging fuel cells and electrolyzers since neutrons can penetrate conventional hardware without requiring special equipment or design modifications.…”
Section: Why We Need X-ray Ct In Electrocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Neutron imaging is a valuable complement to X-ray imaging, since neutrons can penetrate common metals while attenuating hydrogen, lithium, and water. This feature makes neutron imaging an attractive technique for characterizing various electrochemical systems, including fuel cells, water electrolyzers, unitized reversible fuel cells, and CO 2 electrolyzers . Moreover, neutron imaging is particularly well-suited for imaging fuel cells and electrolyzers since neutrons can penetrate conventional hardware without requiring special equipment or design modifications.…”
Section: Why We Need X-ray Ct In Electrocatalysismentioning
confidence: 99%
“…This method involves imaging with hardware rotation, similar to X-ray CT, and has already been reported in several studies. Neutron imaging is widely used to characterize water in various components of fuel cells and electrolyzers, where effective water management is crucial for optimal performance and durability. Specifically, it has been utilized to study water distribution across membrane electrode assemblies, water or oxygen saturation in porous transport layer and gas diffusion layer, as well as the impact of operating conditions . Neutron tomography offers an added advantage by allowing for precise imaging of water distribution in electrochemical systems, thereby providing a better understanding of the heterogeneity present within these systems.…”
Section: Why We Need X-ray Ct In Electrocatalysismentioning
confidence: 99%
“…Several recent studies have demonstrated the capabilities of time‐resolved neutron imaging to study fluid flow in rocks, for example, to reveal the relationship between wormhole advancement and permeability variation in dissolving rocks (Cooper et al., 2023), or to investigate the interactions between imbibition and pressure‐driven flow in microporous deformed limestone (Lewis et al., 2023). Neutron imaging has also been used to study transport properties in other porous media, such as the migration of condensed water vapor through cracked concrete (Gupta et al., 2022), hydro‐channel porous transport layer designed for unitized reversible fuel cells (Komini Babu et al., 2023), as well as salt precipitation and water transport in CO 2 electrolysis (Disch et al., 2022). These studies demonstrate the versatility of the neutron imaging technique and its ability to provide a deeper understanding of fluid transport in various porous media.…”
Section: Introductionmentioning
confidence: 99%